Human Resources Management in International Joint Ventures: Directions for Research - Shenkar, Oded; Zeira, Yoram (Academy of Management Review, 1987)
International joint ventures (IJVs) are becoming more common. This paper classifies the structural characteristics of IJVs and summarizes prevalent personnel problems in IJVs and potential problems that have been overlooked by the human resources literature. A classification of the different employee groups in IJVs is presented and directions for future research are discussed.